Embracing TVET education: The effectiveness of project based learning on secondary school students’ achievement - Zaharah Che Isa; Nurulwahida Azid (Institute of Advanced Engineering and Science, 2021)
Project based learning (PBL) has long been used especially in developing countries. Various results of PBL-related studies have also been found to be effective and have a positive impact on students. However, although it has been introduced in Malaysia, it is still considered foreign to students and teachers. Therefore, this study was conducted to look at the effectiveness of applying the PBL method in the topic of project design on form two students' learning process. An experimental study with mixed method approach was conducted through pre and post-tests on one control and one treatment group. A total of 60 form two students were involved, of which 30 were treatment students and another 30 were control students. Five students from the treatment group were randomly selected to go through a semi structured interview process. This interview was conducted to confirm the results of the quantitative study. The results of analysis of covariance (ANCOVA) showed that students in the PBL group performed significantly better in project design learning process than those in the contrast group. Therefore, this study demonstrated that the PBL method had a positive impact on students' learning process. Based on the interviews, all respondents agreed that PBL was an excellent approach because the learning activities were interesting and different from the normal learning environment. In addition, the interview results also showed that the respondents suggested that the PBL method should be continued and implemented in other topics and subjects.